2020
DOI: 10.1038/s41467-019-13631-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering grain boundaries at the 2D limit for the hydrogen evolution reaction

Abstract: Atom-thin transition metal dichalcogenides (TMDs) have emerged as fascinating materials and key structures for electrocatalysis. So far, their edges, dopant heteroatoms and defects have been intensively explored as active sites for the hydrogen evolution reaction (HER) to split water. However, grain boundaries (GBs), a key type of defects in TMDs, have been overlooked due to their low density and large structural variations. Here, we demonstrate the synthesis of wafer-size atom-thin TMD films with an ultra-hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(187 citation statements)
references
References 78 publications
4
165
0
2
Order By: Relevance
“…[33] It is suggested the nucleation sites and growing rate can be controlled by the flow rate of the vapor sources and seeds density (in Au-quantum-dots-assisted vapor-phase growth). [34] A high flow rate allows more monolayer TMDs with decent sizes of flakes. [35] During transfer, wrinkles, cracks, and other defects can be created in the sample ( Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[33] It is suggested the nucleation sites and growing rate can be controlled by the flow rate of the vapor sources and seeds density (in Au-quantum-dots-assisted vapor-phase growth). [34] A high flow rate allows more monolayer TMDs with decent sizes of flakes. [35] During transfer, wrinkles, cracks, and other defects can be created in the sample ( Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…By DFT calculations, the ΔG H* of the PB could reach À 0.13 eV, which was very close to that of Pt (111) and the Moedge of 2H-MoS 2 (Figure 6c). In order to obtain ultrahigh grain boundary density, He et al [52] prepared wafer-size atom-thin TMDCs films by means of Au-quantum-dots-assisted (Au QDs) vapor-phase growth. By virtue of self-limiting climb and drive growth mechanism, Au QDs not only promoted the initial nucleation of TMDCs, but also limited the domain size of TMDCs below 10 nm (Figure 6d).…”
Section: Grain Boundariesmentioning
confidence: 99%
“…Recently, a facile strategy to combine MoSe 2 and black phosphorus (BP) nano- (f) Corresponding ΔG H of various types of catalytically active sites in MoS 2 catalysts. [52] sheets was described by Li and co-workers. [63] In MoSe -BP heterostructure, the BP served as the 2D substrate to stabilize MoSe 2 from aggregation and provided short pathways for electron transfer, whereas the MoSe 2 contributed abundant active sites for hydrogen adsorption.…”
Section: Two-dimensional Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Grain boundaries (GBs) are normally not preferred because their presence leads to sharp drop of carrier mobility and is detrimental to (opto)electronic device performance. 48,49 However, as revealed in the previous investigations [48][49][50][51][52][53] , GBs, the ubiquitous 2D material defects, can induce intrinsic activation of the 2D basal plane, and thus their presence leads to the signi cant application potential of 2D materials in many other elds including solar cells 54,55 , electrocatalysis 52,56,57 , sensors 26,58,59 , etc. Chen et al 27 have carried out density functional theory (DFT) calculations to reveal the chemical selectivity at GB dislocations in monolayer Mo 1 − x W x S 2 ; Masel et al 26 have reported the realization of ~ 50 times higher sensitivity of polycrystalline graphene based organic vapor sensors compared with pristine single-crystalline graphene lm based sensors; Bao et al 59 have showed that polycrystalline graphene lm can be selectively functionalized with great amount of Pt nanoparticles along GBs for high-sensitivity H 2 sensing; and Liu et al 52 recently reported GB-induced superior hydrogen evolution performance of TMD nanograin lms.…”
Section: Introductionmentioning
confidence: 95%